Answer:
(3, 3 )
Step-by-step explanation:
Given the 2 equations
3x - y = 6 → (1)
6x + y = 21 → (2)
Adding the 2 equations term by term will eliminate y, that is
(6x + 3x) + (y - y) = (21 + 6), that is
9x = 27 (divide both sides by 9 )
x = 3
Substitute x = 3 into either (1) or (2) and solve for y
Using (2), then
(6 × 3) + y = 21
18 + y = 21 ( subtract 18 from both sides )
y = 3
Solution is (3, 3 )
From the graph, we can see that the graph crosses the x-axis at the point (1.5, 0) the graph also passes through point (1, 1) and the graph crosses the y-axis at the point (0, 3).
Therefore, points (1.5, 0), (1, 1) and (0, 3) are some of the solutions of the graph.
Answer:
See below (I hope this helps!)
Step-by-step explanation:
We need to write this in the form y = mx + b.
x + 3y = -12
3y = -x - 12
![y = \frac{1}{3}x - 4](https://tex.z-dn.net/?f=y%20%3D%20%5Cfrac%7B1%7D%7B3%7Dx%20-%204)